PENGEMBANGAN MEDIA PEMBELAJARAN UNBAR BERBASIS ANDROID PADA MATERI UNSUR-UNSUR BENTUK ALJABAR - Yemima, Tyas Sika; Setyadi, Danang (EMTEKA: Jurnal Pendidikan Matematika, 2024)
The aim of this research is to develop and produce Android-based learning materials on algebraic elements. This research includes development research using the ADDIE model which includes analyze, design, development, implement, and evaluation. The instruments used in the research were material expert validation questionnaires, media expert validation, and student response questionnaires. The research results show: (1) The media expert validation results obtained an average score of 95% with a very valid classification, while the material expert validation results obtained an average score of 92% with a very valid classification; (2) Media practicality results in a small-scale trial with research subjects consisting of 10 respondents with an average score of 87% in the very practical category. Thus, Android-based UNBAR learning media tends to be considered to meet the requirements as valid and practical media.